Shopping-centers :elementos de (re)produção urbana na Zona de Sul de Natal-RN - Nascimento, Gerson Gomes do (2003)
This study aims at analysing the (re) prodction of urban space in the south sone of Natal city, in particular the influence of the shopping-centers in this process. In this respect, it also analyses the changes of habits and constumes for part of the society, when those entreprizes were built in better-off areas of the south zone Natal as well as the transformations in the surroundings of the thre main shopping-centers. A sother commercial establishments of the same size, two out of the three main shopping-centers in the city are targered towards the better-off population. However, if compared to the others, one these has, for some time, sought to target a lower in come population. In spite of being an important element in the (re)production of urban space as well as in the cities modern commercial sector, these large commercial entreprizes reinforce capitalisms contradctions in so far as they constitute semi-public space whit an exclusionary and segregatory vatune